(untitled) (Journal of Medicine, 2012)
Acute confusional state account for a substantial proportion of admissions to emergency wards. As the etiology of acute confusional state are numerous and presentation also variable, so many time create confusion regarding the actual diagnosis and thus delay the prompt management which may result in fatal outcome. The objectives of this study was to explore the etiology and age & sex distribution of acute confusional state among hospitalized patients. In this prospective hospital based study, 345 adult patients presenting with acute confusional state were collected from medicine unit Dhaka Medical College Hospital during the period of July’08 to October’08. Patients known to have previous history of stroke, chronic dementing neurological disease were excluded from the study. This study revealed that, patients with acute confusional state constitute about 21% of total hospital admission in medicine wards. Peak incidence of acute confusional state was found to be in two age groups: one in 2nd to 3rd decades and another in 5th to 6th decades. The first peak was due to acute poisoning, CNS infection and hepatic encephalopathy; and the second peak was due to stroke, electrolyte imbalance, systemic infection and disturbance of glucose metabolism. This study also showed male preponderance over female and metabolic causes higher than the structural causes. Stroke comprised the highest percentage (25%) of cases in this series. DOI: http://dx.doi.org/10.3329/jom.v13i1.10047 JOM 2012; 13(1): 46-50